Phenotypic Changes in Mammary Adenocarcinoma (4T1) cells In Vitro after Treatment with Carcinosinum - Silva, Thaís Cristina da; Santos, William Alves dos; Pinto, Sandra A.G.; Rocha, Paulo Ricardo Dell'Armelina; Hurtado, Elizabeth Cristina Perez; Bonamin, Leoni Villano (Homeopathy, 2022)
Objective The present study aimed to identify possible phenotypic changes in 4T1 (murine mammary adenocarcinoma) cells in vitro, including viability, HER-2 (human epidermal growth factor receptor-type 2) expression, and metastatic potential, after treatment with Carcinosinum in different homeopathic dilutions (12cH, 30cH, 200cH) shaken mechanically in pure, sterile, water from a commercial stock dilution.Methods Treated cells were cultured in R10 medium, using 24-well plates, 105 cells per well, and treated with vehicle, Carcinosinum 12cH, 30cH or 200cH; untreated cells were used as the baseline control. After 24 hours of treatment, the percentage of apoptotic cells was analyzed by annexin V. Cell morphology was evaluated by microscopy after hematoxylin-eosin and Giemsa staining, whilst HER-2 expression was assessed using immunocytochemistry. The metastatic potential was determined by the expression and activity of the enzyme matrix metalloproteinase 9 (MMP-9) using zymography. The cytokine profile was established using the cytometric bead array method.Result Treatment of 4T1 cells in vitro with Carcinosinum 30cH produced an increase in the number of annexin V-positive cells (apoptosis) and decreased expression of proactivated MMP-9. Cells treated with Carcinosinum 200cH presented hyper-expression of HER-2 on the plasma membrane, identified by immunocytochemistry. There were no differences in cytokine production among treatments.Conclusion The data show promising results for Carcinosinum 30cH in vitro, but in vivo studies are also required to evaluate the role of tumor microenvironment in its effects.
Keywords: homeopathy; mammary cancer; experimental models